Objectification of the nasal patency assessment techniques used in nasal allergen provocation testing - Krzych-Fałta, Edyta; Samoliński, Bolesław K. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Topical allergen application in nasal provocation testing (NPT) is associated with remarkably rapid changes in nasal patency. Thus, selecting the techniques of assessing the extent of nasal obstruction (as one of the responses to topical allergen application) is an important component of NPT. The study attempted to systematize and evaluate the techniques selected for assessing nasal patency during NPT based on a review of relevant literature. We reviewed the literature on the attempts to standardize the objective techniques for assessing nasal patency and their use in NPT. The best known, well-established technique for assessing nasal patency as part of NPT was rhinomanometry, followed by peak nasal inspiratory flow (PNIF) testing and acoustic rhinometry.